2014
DOI: 10.1371/journal.pone.0090445
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Mapping of Immunodominant Linear B-Cell Epitopes of the Staphylococcus Aureus SEB Antigen Using Short Overlapping Peptides

Abstract: Staphylococcal enterotoxin B (SEB) is one of the most potent Staphylococcus aureus exotoxins (SEs). Due to its conserved sequence and stable structure, SEB might be a good candidate antigen for MRSA vaccines. Although cellular immune responses to SEB are well-characterized, much less is known regarding SEB-specific humoral immune responses, particularly regarding detailed epitope mapping. In this study, we utilized a recombinant nontoxic mutant of SEB (rSEB) and an AlPO4 adjuvant to immunize BALB/c mice and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Therefore, a safe and effective MRSA vaccine is urgently needed. 2 We previously reported a recombination antigen protein vaccine containing alpha-toxin (Hla) gene and iron-regulated surface determinant B (IsdB) gene designed by ourselves. The antibody immune response and protective efficacy were clearly improved after intramuscular immunization with this antigen combined with an aluminum adjuvant in a mouse model of MRSA systemic infection compared with the recombination proteins alone.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a safe and effective MRSA vaccine is urgently needed. 2 We previously reported a recombination antigen protein vaccine containing alpha-toxin (Hla) gene and iron-regulated surface determinant B (IsdB) gene designed by ourselves. The antibody immune response and protective efficacy were clearly improved after intramuscular immunization with this antigen combined with an aluminum adjuvant in a mouse model of MRSA systemic infection compared with the recombination proteins alone.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the cellular fractions that have hundreds of different expressed proteins (Dumpala et al, 2010;Liu et al, 2008) the extracellular fractions have much fewer immunogens, but have been sought for use in the development of vaccines (Zhang et al, 2014). Our analysis found that a single or a very few antigenic determinant(s) were likely immunodominant and initiated the bulk of B-cell responses in these individuals (Vizcaino et al, 1997;Zhao et al, 2014). 368…”
Section: Discussionmentioning
confidence: 85%
“…Thus, part of the aim of this work was to characterize novel SEB binding sdAbs recognizing different epitopes such that they could be used in the development of sandwich-format assays with A3. Three immunodominant epitopes in SEB have been previously identified [21]. The epitopes bound by the sdAbs described here appear to differ from those generated in response to a recombinant SEB.…”
Section: Discussionmentioning
confidence: 87%